Excellent results of screening for subsequent breast cancers in long-term survivors of childhood Hodgkin's lymphoma—Results of a population-based study - Zadravec Zaletel, Lorna; Cesen Mazic, Maja; Jazbec, Janez; Kos, Gregor; Toplak, Miha; Štrbac, Danijela (Frontiers in Pediatrics, 2023)
Introduction: Subsequent breast cancer (SBC) represents a major complication in childhood cancer survivors and screening for SBC in survivors after incidental irradiation of breasts is recommended. In this article, we report the results and discuss benefits of SBC screening in female pts treated for Hodgkin’s lymphoma (HL) in Slovenia in a period of 45 years. Methods: Between 1966 and 2010, 117 females were treated for HL under the age of 19 in Slovenia. One hundred five of them survived for 5 years and were included in our study. They were 3-18 (med. 15) years old at diagnosis and followed for 6-52 (med. 28) years. Eighty-three percent of them had chest RT with a median dose of 30 Gy. Ninety-seven (92%) of 105 pts were regularly followed according to the international guidelines including yearly screening mammography/breast MRI in those who received chest RT. Results: We diagnosed 10 SBCs in eight pts 14-39 (med. 24) years after diagnosis at the age of 28-52 (med. 42) years. At 40 years of follow-up, cumulative incidence of SBCs in females who got chest RT was 15,2%. Seven of eight patients (with 9 SBCs) got chest RT with 24-80 (med. 36) Gy at the age of 12 to 18 (median 17) years. Two patients in this group got bilateral SBC. One patient got invasive SBC after being treated with ChT containing high-dose of anthracyclines without chest RT at the age of 13. All eight invasive SBCs were invasive ductal cancers, HER2 receptors negative, all but one with positive hormonal receptors. Six invasive cancers were of stage T1N0, one T1N1mi, only one, diagnosed before era of screening, was of T2N1. None of 8 pts died of SBC. Conclusion: After introduction of regular breast screening in our female patients, who received chest RT in childhood, all SBCs were of early stage and no patients died of SBC. Survivors of pediatric HL should be informed about the risk of late sequelae of treatment for HL, including SBC. Regular follow-up with breast cancer screening and breast self-examination is of vital importance in those treated with chest RT.